Assessment of availability and challenges of WHO recommended priority life-saving medicines for under five-year children in primary public health facilities of Amhara region - Mastewal Ezezew; Adane Yehualaw; Desalegn Getnet Demsie (BMC, 2023)
Abstract Background The world health organization (WHO) priority lifesaving medicines are medicines recommended for the prevention and treatment of leading causes of under-five morbidity and mortality. They should be available in all health systems and at all times. However, the availability of these medicines and its determinants is not well studied in Ethiopia in general and in primary public health facilities Amhara region in particular. Objective The study aimed to assess the availability and challenges of the WHO-recommended priority lifesaving medicines for under-five children in primary public health facilities of the Amhara region. Methods A cross-sectional study design was conducted from February to December 2020 in 98 health centers and 22 primary hospitals in the Amhara region, Ethiopia. Facilities were selected with a simple random sampling technique. The data were collected through a pretested and structured questionnaire. Binary logistic regression was used to identify predictors associated with availability of WHO-recommended priority lifesaving medicines for under-five children. Results The availability of oral rehydration salt was high (82.5%) and the availability of vitamin A (47.5%), morphine tablet (13.3%), and artesunate rectal suppository (7.5%) were within low and very low WHO range respectively. Budget adequacy (AOR = 12.9 CI= (2.1-78.2)), periodic review of stock level ((AOR = 13.4,CI=(1.9-92.0)), training on integrated pharmaceutical logistic system ((AOR = 4.5,CI=(1.0-20.5)), inclusion of WHO priority under five children facility specific medicine list (AOR = 12.4,CI=(2.3-66.4)), lead time for EPSA(Ethiopia Pharmaceutical Supply Agency) procurement (AOR = 7.9,CI=(1.3-44.8)) were significantly associated with availability of all WHO priority lifesaving medicines for under- five children. Conclusion The average availability of WHO-recommended priority lifesaving medicines for under-five children was low. The habit of updating bincard and adoption of the life-saving medicine list were the independent predictors of medication availability.